The chronic cerebral hypoperfusion model induces proinflammatory cascades in Alzheimer's disease - Abedi, Zahra; Basri, Hamidon; Hassan, Zurina; Inche Mat, Liyana Najwa; Khaza’ai, Huzwah; Mohd Ali, Razana (Neurotak Publishing, 2024)
Cerebral neuroinflammation has emerged as a significant pathway contributing to the progression of Alzheimer's disease (AD) pathology. Research implicates the NOD-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome complex, initiating caspase 1-mediated maturation of interleukin-1 β (IL-1β) and interleukin-18 (IL-18). This study investigates whether chronic cerebral hypoperfusion (CCH), induced via permanent bilateral occlusion of the common carotid arteries (PBOCCA), leads to cognitive dysfunction and NLRP3 inflammasome activation. Twenty male Sprague Dawley (SD) rats underwent PBOCCA to induce CCH. Two weeks post-surgery, locomotor and Morris water maze (MWM) tests were conducted to examine motor functions, spatial learning, and memory, respectively. The gene expression levels of cathepsin B, NLRP3, an apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), and caspase-1 were analysed using real-time PCR, while the expression levels of the inflammatory cytokines were estimated using the ELISA method. Structural damage to the hippocampus was assessed using hematoxylin and eosin (HE) staining. Escape latencies and time spent in specific quadrants in PBOCCA significantly increased compared to sham-operated animals. There was no notable difference in locomotor activity between the PBOCCA and sham-operated groups. The number of pyknotic neurons with cytoplasmic shrinkage increased in the hippocampus. Gene expression of cathepsin B, NLRP3, ASC, and caspase-1 was upregulated in the PBOCCA group. The expression levels of IL-1β, IL-18, interleukin-6 (IL-6), and amyloid-β 1-42 (Aβ 1-42) were elevated in the PBOCCA group relative to sham. The findings confirm NLRP3 inflammasome induction, cognitive dysfunction, and inflammatory cytokines associated with AD and cerebral ischemia. The PBOCCA model provides a valuable tool for studying neurodegenerative including AD.